Lesions of the Rat Perirhinal Cortex Spare the Acquisition of a Complex Configural Visual Discrimination Yet Impair Object Recognition. - Aggleton, John P.; Albasser, Mathieu M.; Aggleton, Duncan J. (Behavioral Neuroscience, 2010)
Rats with perirhinal cortex lesions were sequentially trained in a rectangular water tank on a series of 3 visual discriminations, each between mirror-imaged stimuli. When these same discriminations were tested concurrently, the rats were forced to use a configural strategy to solve the problems effectively. There was no evidence that lesions of the perirhinal cortex disrupted the ability to learn the concurrent configural discrimination task, which required the rats to learn the precise combination of stimulus identity with stimulus placement (“structural” learning). The same rats with perirhinal cortex lesions were also unimpaired on a test of spatial working memory (reinforced T maze alternation), although they were markedly impaired on a new test of spontaneous object recognition. For the recognition test, rats received multiple trials within a single session in which on every trial, they were allowed to explore 2 objects, 1 familiar, the other novel. On the basis of their differential exploration times, rats with perirhinal cortex lesions showed very poor discrimination of the novel objects, thereby confirming the effectiveness of the surgery. The discovery that bilateral lesions of the perirhinal cortex can leave configural (structural) learning seemingly unaffected points to a need to refine those models of perirhinal cortex function that emphasize its role in representing conjunctions of stimulus features. Reprinted by permission of the publisher.